Effect of Paclitaxel and Paclitaxel-Di Allyl Sulfide Combination on 7, 12 Dimethyl Benz (A) Anthracene (DMBA) Induced Skin Cancer in Wistar Rats: A Comparative Study - N. Muninathan, C. Selvakumar, S. Malliga, J. Kumar (Journal of Applied Pharmaceutical Science)
Cancer is a cellular tumor that unlike benign tumor can metastasize and invade the surrounding tissues. In the present study the anticancer effect of paclitaxel was evaluated on 7, 12 Di Methyl Benz (a) Anthracene induced skin cancer in wistar rats and results were compared with normal, paclitaxel and paclitaxel-Di allyl sulfide combined alternative chemotherapy. By analyzing the various biochemical parameters (lipid Profile and lipid metabolizing enzymes) and Marker enzymes (squamous cell antigen). Skin cancer was induced in rats by 7, 12 Di methyl benz(a) anthracene (DMBA) at the dosage of 5 µg was dissolved in 100µl and administered into experimental animals for 28 weeks. In this study, we demonstrated that combination of paclitaxel and Di allyl sulfide protects the rats from a lethal dose of DMBA for 30 days. Total cholesterol (TC), free cholesterol (FC), phospholipids (PL) and triglycerides (TG) were found to be significantly increased whereas ester cholesterol (EC) and free fatty acids (FFA) were significantly decreased when compared with cancer bearing group II animals. From the present study, the effect of Paclitaxel- Di allyl sulfide combination proved to be a more significant chemotherapeutic agent against DMBA induced skin cancer in wistar rats compared to that of paclitaxel by analyzing the lipid profile and lipid metabolizing enzymes and marker enzymes.
Keywords: Skin cancer, 7, 12 Dimethyl benz (a) Anthracene (DMBA), Paclitaxel, Di allyl sulfide.